Transcriptomic and proteomic ramifications of segmental amplification in Escherichia coli - Ryan K. Fritts; Christopher C. Ebmeier; Shelley D. Copley (Proceedings of the National Academy of Sciences, 2025)
Gene amplification can drive adaptation by rapidly increasing the cellular dosage of critical gene products. Segmental amplifications often encompass large genomic regions surrounding the gene(s) under selection for higher dosage. Overexpression of coamplified neighboring genes imposes a substantial metabolic burden. While compensatory mutations can decrease inappropriate overexpression of coamplified genes, it takes time for such mutations to arise. The extent to which intrinsic regulatory mechanisms modulate expression of coamplified genes in the immediate aftermath of segmental amplification is largely unknown. To address the collateral effects of segmental amplification, we evolved replicate cultures of an Escherichia coli mutant under conditions that select for higher dosage of an inefficient enzyme whose weak activity limits growth rate. Segmental amplifications encompassing the gene encoding the weak-link enzyme arose in all populations. Amplified regions ranged in size (33 to 125 kb) and copy number (2 to ≥14 copies). We performed RNA-seq and label-free proteomics to quantify expression of amplified genes present at 2, 6, and 14 copies. mRNA expression generally scales with gene copy number, but protein expression scales less well with both gene copy number and mRNA expression. We characterize the molecular mechanisms underlying discrepancies between gene copy number and expression for several cases. We also show that segmental amplifications can have system-wide consequences by indirectly altering expression of nonamplified genes. Our findings indicate that the fitness benefit derived from segmental amplification depends on the combined effects of amplicon size, gene content, and copy number as well as collateral effects on nonamplified genes.